Adolescent Takayasu's arteritis with hypertensive intracerebral hemorrhage: a case report and literature review - Zhang, Fang; Dong, Bingzi; Yang, Libo; Liu, Jiaxin; Zhan, Jinfeng; Cui, Yukun; Lin, Hua; Wang, Yangang; Lv, Wenshan (Frontiers in Pediatrics, 2024)
Takayasu's arteritis is a primary systemic vasculitis that affects predominantly large vessels, affecting the aorta and its major branches.. We report a case of adolescent female patient who initially experienced numbness and weakness in her limbs, subsequently developing severe hypertension. Physical examination revealed uneven blood pressure in the limbs and a murmur in the auscultation area of the abdominal aorta without decreased pulses. Auxiliary examinations revealed diffuse blood vessel stenosis, leading to the diagnosis of Takayasu's arteritis. One month later, the patient was diagnosed with multiple cerebral hemorrhages following sudden impairment of limb movement. Digital subtraction angiography did not reveal any evident vascular malformations or aneurysms. Following surgery and biologic intervention with tocilizumab the patient's condition improved, with no new bleeding episodes and stable blood pressure control achieved. We also reviewed the literature that have been previously reported with hypertensive intracerebral hemorrhage complicated by Takayasu's arteritis. We recommend that Takayasu's arteritis be taken into account when considering the hypertension in young patients. Timely vascular imaging and standardized treatment are imperative for diagnosing and managing effectively.